- LAHAN SAWAH DILINDUNGI DIKAITKAN DENGAN RENCANA TATA RUANG BERDASARKAN PERATURAN PRESIDEN NOMOR 59 TAHUN 2019 - Diah NikenSari; Meta Indah Budhianti (Reformasi Hukum Trisakti, 2023)
Changes in the conversion of paddy fields in Indonesia often turn into non-agricultural land such as residential development or are designated as strategic projects. This has a serious impact and threatens national food security which is no longer able to meet food needs as the population increases every year. The formulation of the problem is whether the Spatial Plan for Protected Paddy Fields is in Accordance with Presidential Regulation Number 59 of 2019. The research method is normative with the nature of analytical descriptive research using secondary data types and primary data qualitative data analysis, drawing conclusions using deductive logic. The research discussion, not all determination of Paddy Fields is Protected in accordance with the Spatial Plan, miscommunication related to land data that is not reported is a form of obstacle so that the efforts that can be made by the Ministry of ATR/BPN are to provide guidance to stakeholders. Can be concluded that the designation of protected paddy fields associated with spatial planning is still not in accordance with Presidential Regulation Number 59 of 2019 because there are still obstacles in determining LSD where the Central Government and Regional Governments have their own authority which limits the space